Treatment of opioid use disorder in an innovative community-based setting after multiple treatment attempts in a woman with untreated HIV. (11th July 2016) - Voon, Pauline; Joe, Ronald; Fairgrieve, Christopher; Ahamad, Keith
Abstract : Opioid use disorder is associated with significant health and social harms. Various evidence-based interventions have proven successful in mitigating these harms, including harm reduction strategies and pharmacological treatment such as methadone. We present a case of a 35-year-old HIV-positive woman who was off antiretroviral therapy due to untreated opioid use disorder, and had a history of frequently self-discharging from hospital against medical advice. During the most recent hospital admission, the patient was transferred to an innovative community-based clinical support residence that supported harm reduction. Initially, she received methadone to only manage the withdrawal symptoms rather than for long-term maintenance therapy. However, with gradual dose increases to treat cravings and withdrawal, she ultimately discontinued all drug use and reinitiated antiretroviral therapy. This case highlights that patients whose goal is not abstinence can be successfully treated for acute medical illnesses and comorbid substance use disorders using harm reduction approaches, including appropriate dosing of pharmacotherapy.